Dormant but Active: Chilling Accumulation Modulates the Epigenome and Transcriptome of Prunus avium During Bud Dormancy - Rothkegel, Karin; Sandoval, Paula; Soto, Esteban; Ulloa, Lissette; Riveros, Anibal; Lillo-Carmona, Victoria; Cáceres-Molina, Javier; Almeida, Andrea Miyasaka; Meneses, Claudio (Frontiers in Plant Science, 2020)
Temperate deciduous fruit tree species like sweet cherry (Prunus avium) require long periods of low temperatures to trigger dormancy release and flowering. In addition to sequence-based genetic diversity, epigenetic variation may contribute to different chilling requirements among varieties. For the low chill variety ‘Royal Dawn’ and high chill variety ‘Kordia’, we studied the methylome of floral buds during chilling accumulation using MethylC-seq to identify differentially methylated regions (DMRs) during chilling hours (CH) accumulation, followed by transcriptome analysis to correlate changes in gene expression with DNA methylation. We found that during chilling accumulation, DNA methylation increased from 173 CH in ‘Royal Dawn’ and 443 CH in ‘Kordia’ and was mostly associated with the CHH context. In addition, transcriptional changes were observed from 443 CH in ‘Kordia’ with 1,210 differentially expressed genes, increasing to 4,292 genes at 1295 CH. While ‘Royal Dawn’ showed approximately 5,000 genes differentially expressed at 348 CH and 516 CH, showing a reprogramming that was specific for each genotype. From conserved upregulated genes that overlapped with hypomethylated regions and downregulated genes that overlapped with hypermethylated regions in both varieties, we identified genes related to cold-sensing, cold-signaling, oxidation-reduction process, metabolism of phenylpropanoids and lipids, and a MADS-box SVP-like gene. As a complementary analysis, we used conserved and non-conserved DEGs that presented a negative correlation between DNA methylations and mRNA levels across all chilling conditions, obtaining Gene Ontology (GO) categories related to abiotic stress, metabolism, and oxidative stress. Altogether, this data indicates that changes in DNA methylation precedes transcript changes and may occur as an early response to low temperatures to increase cold tolerance in the endodormancy period, contributing with the first methylome information about the effect of environmental cues over two different genotypes of sweet cherry.